Language and the Cultural Practices of Hausa, Igbo and Yoruba People in Nigeria - Ibrahim, Usman (Kashere Journal of Humanities, Management and Social Sciences, 2022)
This study entitled ‘Language and the Cultural Practices of the Hausa, Igbo and Yoruba People in Nigeria’ is designed to find out whether or not language determines the cultural practices of its speakers, using the Hausa, Ibo and Yoruba of Nigeria as the theme. The research adopted two theories to work with: linguistic determinism and Social Cohesion. To achieve the objective of this study, linguistic tools such as words, proverbs, worldviews and praise-epithets relating to food, clothing and politics were fully utilized. Moreover, the three ethnic groups’ behavioral patterns on dresses, dishes, literature, languages, historical and religious bases were collected using structural interview questions. 100 respondents were interviewed from each of the selected ethnic groups. The respondents were selected using purpose sampling techniques. T-test statistical tool was employed in analyzing the responses of the respondents in determining the differences in cultural practices among the selected ethnic groups. The finding of the study revealed statistical significant differences between Hausa, Igbo and Yoruba. In addition, this research revealed the manners and behaviors’ of each mentioned ethnic groups.